2016
DOI: 10.1002/eqe.2787
|View full text |Cite
|
Sign up to set email alerts
|

R/C frame–infill interaction model and its application to Indonesian buildings

Abstract: SUMMARYThis paper proposes a new analytical model for masonry-infilled R/C frames to evaluate the seismic performance considering R/C frame-infill interactions. The proposed analytical model replaces masonry infill with a diagonal compression strut, which represents distributed compression transferred between frame and infill interfaces. The equivalent strut width is presented as a function of the frame-infill contact length, which can be evaluated by static equilibriums related to compression balance and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
0
29
0
2
Order By: Relevance
“…Penulis juga telah mengembangkan sebuah metoda analisis dinding bata dalam struktur rangka (Maidiawati et. al, 2012(Maidiawati et. al, , 2013.…”
Section: Pendahuluanunclassified
“…Penulis juga telah mengembangkan sebuah metoda analisis dinding bata dalam struktur rangka (Maidiawati et. al, 2012(Maidiawati et. al, , 2013.…”
Section: Pendahuluanunclassified
“…Masonry walls are ubiquitously used as infill in reinforced concrete (RC) frame structure buildings in high seismic region. According to post-earthquake observation results, the presence of masonry infills influenced the behavior of RC building during an earthquake [1,2]. The results of the previous studies have been summarized that unreinforced brick masonry infill contributes to increase the lateral strength and stiffness but decrease the ductility of infilled RC frame structures [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This issue is caused by the shortage of the knowledge of the performance of brick wall under seismic loads. Several experimental and analytical studies have been reported that masonry infills strongly affected seismic performance of RC buildings [1][2][3][4][5]. Nevertheless, most of them concentrated to study the seismic behaviour of RC frame buildings using the solid masonry wall.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of them concentrated to study the seismic behaviour of RC frame buildings using the solid masonry wall. In the previous study, the first author also has calculated the seismic capacity of RC buildings including the contribution of brick masonry infill by applying a developed analytical model of infill frame [3]. But, the presence of brick infills with openings was excluded in evaluation which guessed that no contribution from the infills with openings on the earthquake resistance of RC frame structures as reported on the Reference [6].…”
Section: Introductionmentioning
confidence: 99%